Land planning and protected areas in the coastal zone of Mexico: Do spatial policies promote fragmented governance?. (October 2022) - Bazant-Fabre, Ondrej; Bonilla-Moheno, Martha; Martínez, M. Luisa; Lithgow, Debora; Muñoz-Piña, Carlos
Abstract: Coastal areas host nearly 30 % of the world population and are among the most diverse and disturbed environments on Earth. In consequence, spatial policies have been implemented to manage this socio-ecological complexity from different perspectives. Protected Areas (PA) and Land Planning (LP) have been co-implemented worldwide, but they have divergent objectives: the former seeks ecosystem preservation, while the latter seeks land use development. Despite the importance PA and LP have in coastal management worldwide, we found little information on how they interact and what effects does this policyscape have on the coastal landscape. To bridge this information gap, this paper proposes a novel method to assess the interaction of overlapping PA and LP, by employing land cover and population density proxy indicators in order to determine if they are complementary or inhibitory. Using the terrestrial coast of Mexico as a case study, we found that all coastal regions exhibited overlaps between PA and LP: from the 101 instruments analyzed, 60.4 % showed overlap but they only corresponded to 5.9 % of the total Mexican terrestrial coast. The similarities between the natural cover type in PA and its overlap with LP (both ≈89 %) suggest that a complementary interaction between both instruments exists in the terrestrial coast of Mexico. Nevertheless, our results found that overlapped PA had 11 % of anthropic cover and a slightlu y higher population density (62 people/km 2 ) than PA alone (11.5 people/km 2 ), which suggests that LP can have deleterious effects through spillover effects due to poorly integrated buffer zones and LPs' planning hierarchy. Therefore, evidence from our results and international research suggests that a lack of integration between both spatial policies should be further addressed, especially at local case studies within regional scopes. We discuss on how the fragmentation between these spatial policies can be further assessed using allocation and attribution frameworks, concluding on integrated recommendations to Mexican coastal authorities. Our results and conclusions can be useful to other countries with similar coastal characteristics. Highlights: The interaction between protected areas (PA) and land planning (LP) on the policyscape of costal zones has not been addressed. Land cover and population density are proxies to evaluate if the interaction between PA and LP is complementary or inhibitory. In the Mexican coastal zone, PA and LP have complementary interactions, promoting the preservation of natural cover.